2009
DOI: 10.1016/j.adt.2009.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Complementary optical-potential analysis of -particle elastic scattering and induced reactions at low energies

Abstract: A previously derived semi-microscopic analysis based on the Double Folding Model, for α-particle elastic scattering on A ∼100 nuclei at energies below 32 MeV, is extended to medium mass A ∼50-120 nuclei and energies from ∼13 to 50 MeV. The energy-dependent phenomenological imaginary part for this semi-microscopic optical model potential was obtained including the dispersive correction to the microscopic real potential, and used within a concurrent phenomenological analysis of the same data basis. A regional pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
175
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(193 citation statements)
references
References 108 publications
14
175
0
Order By: Relevance
“…The analysis of α-induced reaction cross sections below the Coulomb barrier [6] has shown that the diffuseness a R of the OMP real part as well as the surface imaginary potential depth W D , established by the former analysis above B, are responsible for the difficulties encountered in the description of the reaction data at lower energies. Consequently, the modified energy dependence of these two parameters, for E c.m.…”
Section: Additional α-Particle Optical Potential Test Below the Coulomentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis of α-induced reaction cross sections below the Coulomb barrier [6] has shown that the diffuseness a R of the OMP real part as well as the surface imaginary potential depth W D , established by the former analysis above B, are responsible for the difficulties encountered in the description of the reaction data at lower energies. Consequently, the modified energy dependence of these two parameters, for E c.m.…”
Section: Additional α-Particle Optical Potential Test Below the Coulomentioning
confidence: 99%
“…/B <0.9 (Table 3 of Ref. [6]) have provided an optical potential that describes equally well the low energy α-particle-induced reaction and elastic scattering data. This has been additionally proved [8] to be also the case of recent analysis of the (α,n) reactions on 92,94 Mo isotopes and α-capture on 112 Sn [3] and 117 Sn [4].…”
Section: Additional α-Particle Optical Potential Test Below the Coulomentioning
confidence: 99%
See 2 more Smart Citations
“…For outgoing alpha-particles, we adopted the recent version of the global OMP of Avrigeanu et al [29,30]. Calculations are done using the ECIS code [31] assuming the spherical model.…”
Section: Optical Model Potentialmentioning
confidence: 99%